Clinicopathologic characteristics and management of minute esophageal lesions diagnosed by narrow-band imaging endoscopy - Kumamoto, Takashi; Sentani, Kazuhiro; Oka, Shiro; Tanaka, Shinji; Yasui, Wataru (Endoscopy International Open, 2016)
Background and study aims: Magnifying narrow-band imaging (NBI) endoscopy enables the diagnosis of minute esophageal neoplasia. We aimed to evaluate clinicopathological diagnosis of minute esophageal neoplasia by using magnifying NBI endoscopy and biopsy.Patients and methods: In total, 309 patients (127 men and 182 women) with minute esophageal lesions of intrapapillary capillary loop (IPCL) type IV were enrolled. Of these patients, 249 underwent biopsy for histologic diagnosis and also for treatment. Of the 249 patients, 123 underwent follow-up with endoscopy. We analyzed the clinicopathologic characteristics and prognosis of these lesions after biopsy.Results: Of the 249 biopsied lesions, we histologically diagnosed 11 as high-grade intraepithelial neoplasia (HGIN), 41 as low-grade intraepithelial neoplasia (LGIN), and 197 as non-neoplasia (Non-N) including inflammation. Six of the 11 HGINs and 11 of the 41 LGINs showed slight elevation. Background coloration was observed in 9 of 11 HGINs, 34 of 41 LGINs, and 33 of 197 Non-Ns. Of the 249 biopsied lesions, 147 were microscopically measurable. The average diameter was 1.4 mm for HGINs and 0.8 mm for LGINs. Of the 123 patients who underwent post-biopsy follow-up, 93 (76 %) showed no lesions at the biopsied sites during the NBI examinations and were suspected to have undergone complete resection by biopsy. Conclusions: Biopsy was useful for diagnosis and treatment of minute esophageal lesions, diagnosed as IPCL type IV by magnifying NBI endoscopy.